Effect of early postnatal nutrition on chronic kidney disease and arterial hypertension in adulthood: a narrative review. (6th August 2018) - Juvet, C.; Simeoni, U.; Yzydorczyk, C.; Siddeek, B.; Armengaud, J.-B.; Nardou, K.; Juvet, P.; Benahmed, M.; Cachat, F.; Chehade, H.
Abstract: Intrauterine growth restriction (IUGR) has been identified as a risk factor for adult chronic kidney disease (CKD), including hypertension (HTN). Accelerated postnatal catch-up growth superimposed to IUGR has been shown to further increase the risk of CKD and HTN. Although the impact of excessive postnatal growth without previous IUGR is less clear, excessive postnatal overfeeding in experimental animals shows a strong impact on the risk of CKD and HTN in adulthood. On the other hand, food restriction in the postnatal period seems to have a protective effect on CKD programming. All these effects are mediated at least partially by the activation of the renin–angiotensin system, leptin and neuropeptide Y (NPY) signaling and profibrotic pathways. Early nutrition, especially in the postnatal period has a significant impact on the risk of CKD and HTN at adulthood and should receive specific attention in the prevention of CKD and HTN.